2016
DOI: 10.1002/cem.2805
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of the inverse Gaussian regression residuals for the assessment of influential points

Abstract: Influential analysis is the main diagnostic process to obtain reliable regression results. Same is true for the generalized linear model. The present article empirically compares the performance of different residuals of the inverse Gaussian regression model to detect the influential points. The inverse Gaussian regression model residuals are further divided into two categories, that is, standardized and adjusted residuals. Cook's distance has been computed for both of the stated residuals, and then comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…GLM has three components: a response variable distribution, a linear predictor η = X ′ β that involves the regression variables, and a link function η i = g ( μ i ) that connects the linear predictor to the natural mean of the response variable. The data we are using follows the inverse Gaussian distribution, and resultantly the IGRM . For inverse Gaussian regression, inverse squared canonical link function is used: Link function()=μ2 and Mean function()μ=12 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…GLM has three components: a response variable distribution, a linear predictor η = X ′ β that involves the regression variables, and a link function η i = g ( μ i ) that connects the linear predictor to the natural mean of the response variable. The data we are using follows the inverse Gaussian distribution, and resultantly the IGRM . For inverse Gaussian regression, inverse squared canonical link function is used: Link function()=μ2 and Mean function()μ=12 …”
Section: Methodsmentioning
confidence: 99%
“…This data set is already used by Meloun and Mility, for detection of influential observations in LRM and found observation numbers 12, 14, 29, 33, and 34 as influential. Amin et al also used this data and detect influential points through IGRM as GLM because response variable follows inverse Gaussian distribution. They have shown that observations 5, 12, 14, 26, 27, 28, 29, and 30 are influential.…”
Section: Empirical Evaluationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to Amin et al , in the GLM approach, the PRs are defined as χ=ytrueμ^Vartrueμ^. Therefore, the PR of the IG regression can be written as follows: χ=y1Xβ1Xβ3. …”
Section: The Data Model For the Glm‐based Control Chartmentioning
confidence: 99%